Title of Study: Comparative Evaluation of Dexmedetomidine And Clonidine As An Adjuvant To Ropivacaine For Epidural Anaesthesia In Lower Abdominal Surgeries - Varghese, Suzanna; Taksande, Karuna; Singam, Amol (International Journal of Psychosocial Rehabilitation, 2020)
Background: Owing to its sedative and analgesic properties, alpha 2 adrenergic agonists improve the quality and duration of regional anaesthesia when added as an adjuvant. Objectives: The study objective was to evaluate and compare Ropivacaine given epidurally when given in combination with dexmedetomidine as compared to clonidine in terms of efficacy with emphasis on their onset and duration of action, haemodynamic stability and sedation. Methods: The study will be conducted in prospective, randomized manner. It will include 80 patients with ASA physical status I,II who are to undergo a lower abdominal procedure under epidural anaesthesia. Patients will be grouped into 2 randomly of 25 people each. Group RC will be given 15ml of 0.75% Ropivacaine and injection Clonidine 2mcg/kg epidurally. Group RD will be given 15ml of 0.75% Ropivacaine and injection Dexmeditomidine 1.5mcg/kg epidurally. The parameters assessed will be the haemodynamic stability, motor and sensory block onset and duration and sedation. Results: We hypothesize that both the groups will not show any significant difference in surgical characteristics or demographically and group RD will show better sedation scores and significantly shorter time of onset of blockade of motor and sensory innervation and also longer duration of analgesia as compared to group RC. Conclusion: We anticipate concluding that dexmedetomidine will be a superior neuraxial adjuvant to Ropivacaine for faster onset of analgesia, sedation and stable haemodynamic parameters as compared to clonidine.